Effects of haze pollution and institutional environment on demand for commercial health insurance - Jia, Pan; Yan, Jingshi (Frontiers in Psychology, 2022)
Using the cross-sectional data of the China Household Finance Survey (CHFS) in 2017, this paper analyzes the impact of haze pollution on Residents' demand for commercial health insurance and the heterogeneous effect of the institutional environment on this impact. The study found that with the improvement of residents' health risk awareness, haze pollution increased residents' demand for commercial health insurance. Under the influence of the institutional environment, the hedging function of commercial health insurance for haze pollution shows obvious result heterogeneity. In high-level legal and market environments, haze pollution will increase the probability of residents purchasing commercial health insurance; on the contrary, this probability will be reduced. The influence of traditional culture on this relationship shows the opposite result. Further analysis shows that the relationship between haze pollution and residents' demand for commercial health insurance will show obvious regional heterogeneity. They are significantly positively correlated in the eastern regions, while they are significantly negatively correlated in the central and western regions. In addition, residents' preventive behavior will be substantially different due to individual risk preferences in the face of haze pollution. The conclusion of this paper is of great significance to improve public health risk awareness, optimize the business environment, and promote the rapid development of commercial health insurance.